ChemInform Abstract: Unusual C—S Bond Cleavage in Hydro(solvo)thermal Reaction that Induces Two Novel Nickel Thiolates: The Crown [Ni16(edt)8S9(S2)]4‐ with an Unprecedented 12‐Membered Ring System and the Cagelike [Ni13(edt)8S4(S2)2] 2‐ with Two Distorted Cores. Issue 3 (21st January 2014) - Jiang, Hao; Sheng, Tianlu; Bai, Songyan; Hu, Shengmin; Wang, Xin; Fu, Ruibiao; Yu, Peng; Wu, Xintao
Abstract The crystal structures of compounds (II) and (III) are determined by single crystal XRD.